Rasuras no "chão dos lobos" : A poética de fronteira de Charles Trocate - Souza, Airton (2020)
Erasures on the “floor of the wolves” - Charles Trocate's frontier poetics is the result of two tumultuous years of research, above all because of the political uncertainties that currently overwhelm the country. Under the guidance of Prof. Dr. Gilson Penalva, this work was destined to the Master's Program in Letters, by the Federal University of the South and Southeast of Pará. In addition, Rewritten at least three times during these years this book is part of a testimony of the now. From a poetics centered on the provision of action. Converging to the state of the timeless immediate. This is precisely one of the most essential issues in Amazonian poetics. Because in that space all struggles converge for today. This is mainly because the executioners do not sleep. They are nourished by the only feeling of forbidding us to love our land, showing it only as an economic potential and at the same time outlining traces of impotence in our feelings. Here are the testimonies of small border readings in Charles Trocate's poetics. This is one of the most active scriptures on the front in the Amazon. Because Trocate is, as Luiz Ricardo Leitão wrote, “a caboclo combatant armed with words”. For the poet, the word is practical, and he knows that it is capable of causing discomfort at the heart of those who only think incessantly to rob the Amazonian being and geography. That is why the word is salt, and it subverts, when questioning the values ​​and power in this process of plunder. Based on a poetics of action, Trocate gives us the sincere right to look at the different realities that plague our borders on a daily basis, be they: subjective, collective, real or imaginary. The semantic charge in Trocate's poetic expression is multifaceted. It causes disruptions in the immediate way of crossing the Amazon. It crosses both cities and fields, while embracing the sentimental preludes flagged by an infinity of comrades. Thus, Charles Trocate transfigures realities, making them other symbolic constructions within those realities. In his poetics, he rewrites plural meanings, seeking to interpret the moment, while still contesting it. He makes his poetry the space of affection and combat, as if he knows how to cross the trenches with all the political horizons disturbing his retinas. Or who wants much more than the silenced introito. Not for nothing, we will see in this Rasuras on the “floor of the wolves” - Charles Trocate's frontier poetics, how much the trocatian poetics becomes more and more intense in the temporal and territorial urgency. Making the possibility of becoming a surprising symbolic field, by maintaining an intrinsic relationship with everyday life in the Amazon and the transposition of that relationship into the poetic word. While Charles Trocate stretches the processes of political and literary senses. Because of this, this book approaches the process of neglect from two symbolic elements in trocatian poetics, which are: border poetry as a pedagogical act and political-daily aesthetic analysis. Both are pervaded by dialogues metaphorically linked to temporalities, based on verbal analysis, and territorialities, analyzing how the procedures for intensifying metaphors enhance symbolic representation. We will see in large part that the enunciative locus of Charles Trocate's poetics is the Amazon. It is from these geographies that the symbologies of his words seek to reorganize, even if questioning, the actions marked by differences, centered on forms of power. Thus, the poet points out other possible speeches. Except that speeches of those who are inside the front, and not as always historically happened, the discursive construction of the Amazon by those who are outside, creating stereotypes as a domination project. With a poetic conception that stresses the symbolic forms of the words Charles Trocate contributes to the expansion of several problems existing in the Amazon, as we will see exemplified throughout this book. And, in this perspective, he conceives other ways of seeing ourselves critically. In this way, Trocatian poetics displaces the official story about the critical thoughts regarding the subjects and Amazonian territorialities. We have, therefore, in this Rasuras on the “floor of the wolves” - Charles Trocate's border poetics not as the end point, but as the territorial and temporal possibility of the place to leave.